1999
DOI: 10.1001/archinte.159.18.2161
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Assessment of the Omeprazole Test in Patients With Symptoms Suggestive of Gastroesophageal Reflux Disease

Abstract: Objective: To evaluate the diagnostic accuracy of a trial of a high-dose proton pump inhibitor (the omeprazole test) in detecting gastroesophageal reflux disease (GERD) in patients with heartburn symptoms.Design: A randomized, double-blind, placebocontrolled, crossover trial.Patients and Setting: Forty-three consecutive patients with symptoms suggestive of GERD were enrolled at a Veterans Affairs medical center.Main Outcome Measures: Symptom response to the omeprazole test vs placebo in GERD-positive and GERDn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
133
2
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(140 citation statements)
references
References 20 publications
1
133
2
4
Order By: Relevance
“…11 For example, two studies revealed that 22 and 26% of patients with upper endoscopy documented erosive oesophagitis manifested normal 24-h pH probe test results. 12,13 Finally, in clinical practice the 24-h pH probe is not indicated for the routine evaluation of GERD but instead for the diagnosis of atypical symptomatology and for the assessment of subjects considering antireflux surgery. 14 Upper endoscopy also suffers flaws as a tool for diagnosing GERD.…”
Section: Introductionmentioning
confidence: 99%
“…11 For example, two studies revealed that 22 and 26% of patients with upper endoscopy documented erosive oesophagitis manifested normal 24-h pH probe test results. 12,13 Finally, in clinical practice the 24-h pH probe is not indicated for the routine evaluation of GERD but instead for the diagnosis of atypical symptomatology and for the assessment of subjects considering antireflux surgery. 14 Upper endoscopy also suffers flaws as a tool for diagnosing GERD.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, these patients were not found to have evidence of either peptic ulcer or GERD after having undergone upper endoscopy, 24-hour ambulatory pH monitoring, and a therapeutic trial of high-dose PPI therapy. 26 Although not included as "successes" in our final analysis, it further illustrated the usefulness of a disease-oriented pharmacy clinic to optimally manage GERD patients. The use of nonphysicians to implement clinical practice guidelines was unique as it applied to this setting of reflux patients.…”
Section: Discussionmentioning
confidence: 98%
“…Questionnaires and symptom records were used in most studies for the assessment of PPI response; although the symptom response threshold varied according to the study, in comparison with the beginning of the test, a 50%-75% recovery in symptoms was acceptable. A significant difference was not detected among PPIs in terms of effectiveness (10-12).Although the sensitivity of the PPI test is 27%-89% in patients with typical symptoms of GERD, its specificity is 35%-83% (2,(4)(5)(6)(7)(8)13,14). Because of the use of different methods and populations in studies, it is quite difficult to make comparisons.…”
mentioning
confidence: 99%
“…Although the sensitivity of the PPI test is 27%-89% in patients with typical symptoms of GERD, its specificity is 35%-83% (2,(4)(5)(6)(7)(8)13,14). Because of the use of different methods and populations in studies, it is quite difficult to make comparisons.…”
mentioning
confidence: 99%